INFLUENCE OF MODERN FINANCIAL TECHNOLOGIES ON THE INSTITUTIONAL STRUCTURE OF THE RUSSIAN BANKING SYSTEM - A. V. Berdyshev (Вестник университета, 2019)
The conditions, that stimulate the development of financial technologies in the banking sector, as well as the main directions of development of mobile technologies in the banking sector, have been defined. Based on the construction of a regression model, the impact of the development of mobile technologies on the institutional composition of the Russian banking system has been assessed, indicating, that with increased usage of the Internet and mobile technologies in the process of making customer payments, the number of internal structural units of existing credit institutions is reduced.